Combined Effect of Bhramari and Nadi Shodhan Pranayama on Anger Control among Security Personnel at Eastern India – An Experimental Study - Harh, Dishani; Paniyadi , Nanda Kumar; Sahoo, Prasanta Kumar; Sahu, Santosh Kumar; Kumari, Anuradha; Singh, Priyanka; Lytton, Roshna (International Research Journal of Ayurveda & Yoga, 2025)
Background: Anger is a natural emotion, experienced by every individual. When it is uncontrollable and devastative, it can cause various physiological, psychological, and behavioral problems. Pranayama is very effective in reducing stress, anxiety, and anger. Security personnel are working in the front line and being called to safeguard others in high-risk situations. They are more prone to get injured at the workplace with unexpected attacks than any other professionals. Aim: The aim of this study was to assess the anger among security personnel and the effect of Bhramari and Nadi Shodhan pranayama on anger control. Materials and Methods: The study was conducted at the AYUSH Department of Tertiary Care Hospital of Eastern India. Pranayama was planned for anger control, which consisted of Bhramari and Nadi Shodhan pranayama, to be taught to 40 security personnel in a 2-week period. Anger was assessed by using a self-structured ‘Anger Self-Report Questionnaire’. Results: A significant reduction in anger was found in the experimental group compared with a control group. Conclusion: Bhramari and Nadi shodhan pranayama were found to be effective for anger control among security personnel.